Understanding regulations, tax sanctions and taxpayer compliance: the role of risk preference moderation - Egha Nurwati; Umaimah Umaimah (Jurnal Akademi Akuntansi)
Purpose: This study aims to provide empirical evidence empirical evidence related to tax knowledge and tax sanctions with risk preference as moderating preference as a moderator for increasing taxpayer compliance.